Human Rights Risks in the Constitutions of the American Federal States - Markhgeym, Marina V.; Novikova, Alevtina E.; Dmitriev, Vladimir K.; Dzidzoev, Ruslan M.; Larina, Ol’ga G. (International Journal of Criminology and Sociology, 2022)
The article presents the results of a comparative legal analysis of the constitutions of American federal states (Argentina, Brazil, Venezuela, Canada, Mexico, and USA) with a view to identifying the norms that minimize human rights risks. The examination depended on an argumentative way to deal with the revelation of legitimate wonders and cycles utilizing general logical (precise and consistent strategies, investigation and amalgamation) and explicit logical techniques. The declared axiological, functional, and institutional parameters are fully set only in the Constitution of Venezuela. Other constitutions that consider the objective specifics of the historical development of countries reflected the desired formulations in the framework of the axiology of individual rights and freedoms; prohibition of slavery; judicial protection of individual rights; isolation of a special human rights institution, etc. The objectives of the study led to the use of special legal methods. Thus, the comparative legal method contributed to the identification of resources and means of minimizing risks to human right advocacy in the foreign constitutions. The novelty of this research is identifying the norms that minimize human rights risks.